The Investigation of Terminal Segment Effect on Blood Pressure Propagation Patterns in Cardiovascular System Models - Daniela Gombarska; Barbora Czippelova; Ivo Cap (Communications - Scientific letters of the University of Zilina, 2011)
The electro-mechanical analogy method is used for the simulation of blood flow in blood vessels. Particularly the subject of this paper is the investigation of the influence of terminal segment topology on the blood pressure propagation patterns. The cardiovascular system is widely branched and therefore very complex. Thus, it is impractical to create the simulation model consisting of all blood vessels and attention is focused to development of models for smaller parts of vascular system. The selection and adjustment of terminal segments for such simulation model is important on behalf of the model accuracy. Three different types of terminal segments were implemented in order to show their influence to the blood pressure and blood flow propagation patterns in two model complexities.